Práctica preprofesional en la Universidad Nacional de Educación (UNAE): análisis y reflexiones de la modalidad virtual en tiempos de pandemia - Pesántez Palacios, Maria Dolores; Cuenca Alvarado, Paola Alexandra (Universidad de Costa Rica, 2022)
This article provides elements of a research conducted in 2020 in which the debate on the importance of pre-professional practice (PP) or pedagogical practice in face-to-face mode for the training of research teachers with an inclusive profile is expanded. At the National University of Education (UNAE-Ecuador), PP is considered the backbone of professional training. In the year 2020 due to the pandemic, the Special Education career implemented in the academic period April-August 2020 the virtual modality for PP, with the support of the Regular Educational Units and Specialized Education. This is a qualitative study, applying the participatory method from the perspectives of the main actors of the PP: students, professional tutors (school teachers) and academic tutors (UNAE teachers). Information was obtained from various sources: online questionnaires, documentary review and a focus group. The results suggest that pre-professional practice in virtual mode does not guarantee quality training processes for future teachers. Face-to-face PP provides more efficient spaces for reflection on experiences related to practice and the relationship established between theory and practice as fundamental pillars in teacher training. On the other hand, virtual PP limits the contact of the practitioner with the socio-educational reality, a situation that has prevented the establishment of adequate processes of reflection on teaching practice and identification of needs and problems in the different socio-educational contexts. Key words: inclusive education, special education, teacher training, pedagogical practice